Pelatihan Keterampilan Produktif Untuk Meningkatkan Kemandirian Ekonomi Masyarakat - Isa, Abd. Hamid; Anu, Zulkarnain (Universitas Negeri Gorontalo, 2024)
Implementation of Thematic Real Work Lectures with the target of realizing villages that have advantages and sustainable competitiveness has good added value if synergized with productive skills training programsto increase economic independence for village people. This is important because the village area with its various potentials is a priority program for universities to intervene both in terms of education policy and efforts to accelerate economic resilience which has an impact on increasing the income and welfare of its people. A productive skills program implemented in the form of training for the community so that they have the knowledge, attitudes and skills needed to deal with problems both related to self-development and life behavior as well as strengthening efforts for community economic independence. The target of this study is as reference material that can be used both for the development of scientific studies, as input for stakeholders and practitioners engaged in community empowerment to carry out movements to enable and develop communities in an integrated and sustainable manner in improving the quality of life through productive skills training that is economically valuable and benefit the village community. The achievement of this activity is the implementation of productive activities for the target community, namely Productive Skills Training for Economic Independence (Tourism Destination Management Training and Agricultural Waste Utilization Processing Training). Communities have been educated and enthusiastic about implementing various potential programs in their environment because they have the right and authority to determine what they should need. It is recommended that activities that have been successfully carried out in the form of community service need to be continued and improved as an effort to empower the community for economic independence which is very beneficial for increasing the income and quality of life of rural communities.